Metalização mecânica de ZrO2 com Ti para brasagem ZrO2/Aço com ligas de adição sem metal ativo - Silva, João Moreno Vilas Boas de Souza (2011)
Metal/ceramic interfaces using zirconia have dominated the industrial applications in the last decade, due to the high mechanical strength and fracture toughness of zirconia, especially at temperatures below 300 ºC. Also noteworthy is the good ionic conductivity in high temperatures of this component. In this work joining between ZrO2 Y-TZP and ZrO2 Mg-PSZ with austenitic stainless steel was studied. These joints were brazed at high-vacuum after mechanical metallization with Ti using filler alloys composed by Ag-Cu and Ag-Cu-Ni. The influence of the metallization, and the affinity between the different groups (ceramic / filler alloys) was evaluated, in order to achieve strong metal/ceramic joints. Evaluation of joints and interfaces, also the characterization of base materials was implemented using various techniques, such as: x-ray diffraction, leak test, three-point flexural test and scanning electron microscopy with chemical analysis. The microstructural analysis revealed physical and chemical bonds in the metal/ceramic interfaces, providing superior leak proof joints and stress cracking, in order to a good joint in all brazed samples. Precipitation zones and reaction layers with eutetic characteristics were observed between the steel and the filler metal